Crosstalk between inflammation, iron metabolism and endothelial function in Behçet’s disease - Oliveira, R. (2014)
Behçet's disease (BD) is a rare chronic vasculitis of unclear etiology. It has been suggested that inflammatory response has an important role in BD pathophysiology. Herein, we aimed to study the interplay between inflammation, iron metabolism and endothelial function in BD and search for its putative association with disease activity. Twenty five patients clinically diagnosed with BD were selected and twenty four healthy age-sex matched individuals participated as controls. Results showed an increase of total number of circulating white blood cells and neutrophils, serum transferrin, total iron binding capacity, mieloperoxidase (MPO), ceruloplasmin (Cp), C reactive protein, β2 microglobulin and Cp surface expression in peripheral blood monocytes in BD patients comparatively to healthy individuals (p < 0,05). Of notice, the alterations observed were associated to disease activity status. No significant differences between the two groups were found in serum nitric oxide concentration. The results obtained suggest an important contribution from innate immunity in the pathogenesis of this disease. In particular, surface expression of leukocyte-derived Cp may constitute a new and relevant biomarker to understand BD etiology.